Biss+Kuss : 9. Berner Kunstausstellung. - Kunsthalle Bern, Bern (Bern : Kunsthalle Bern, 1982)
Dickerhof, Urs ; Güdel, Ulrich ; Knöpfli, Jetzt ; Kuhn-Klein, Claude ; Marmet, Peter ; Beutler, Maja ; Reich, Heidi ; Roth, Max ; Ruegg, Ilona ; Timmermahn
Biss+Kuss : 9. Berner Kunstausstellung, Kunsthalle Bern, 9. Oktober - 14. November 1982
boek